2011
DOI: 10.1016/j.actamat.2011.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Stability of nanoscale secondary phases in an oxide dispersion strengthened Fe–12Cr alloy

Abstract: A c t a M a t e r i a l i a 5 9 ( 2 0 1 1 ) , p p . 3 9 2 7 -3 9 3 6 DO I : h t t p : / / d x . d o i . o r g / 1 0 . 1 0 1 6 / j . a c t am a t . 2 0 1 1 . 0 3 . 0 1 7 © 2 0 1 1 A c t a M a t e r i a l i a. E l s e v i e r L t d . I n s t i t u t i o n a l R e p o s i t o r y S t a b i l i t y o f n a n o s c a l e s e c o n d a r y p h a s e s i n a n o x i d e d i s p e r s i o n s t r e n g t h e n e d F e 1 2C r a l l o y V . d e C a s t r o a , ⇑ , E .A . M a r q u i s a , 1 , S . L o z a n o -P e r e z … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(50 citation statements)
references
References 35 publications
5
45
0
Order By: Relevance
“…In the HRTEM studies on the Fe-Y 2 O 3 alloy, ten oxide particles were analyzed and only one, with a diameter of 12 nm, was found to be monoclinic yttria and the rest of them bcc Y 2 O 3 . Our starting powder was bcc Y 2 O 3 and bulk yttria is most stable in the bcc phase up to 2598 K at atmospheric pressure [46][47][48], whereas nano-scale Y 2 O 3 particles are stabilized in the monoclinic phase owing to the increasing importance of surface effects [19,46,49]. Chang et al [50] also studied phase transformations in nano-scale Y 2 O 3 using electron microscopy and concluded that the critical grain size for the monoclinic to cubic transformation is in the range of 8-12 nm.…”
Section: Discussionmentioning
confidence: 99%
“…In the HRTEM studies on the Fe-Y 2 O 3 alloy, ten oxide particles were analyzed and only one, with a diameter of 12 nm, was found to be monoclinic yttria and the rest of them bcc Y 2 O 3 . Our starting powder was bcc Y 2 O 3 and bulk yttria is most stable in the bcc phase up to 2598 K at atmospheric pressure [46][47][48], whereas nano-scale Y 2 O 3 particles are stabilized in the monoclinic phase owing to the increasing importance of surface effects [19,46,49]. Chang et al [50] also studied phase transformations in nano-scale Y 2 O 3 using electron microscopy and concluded that the critical grain size for the monoclinic to cubic transformation is in the range of 8-12 nm.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10]. The more relevant characteristics of the alloys can be summarized as follows: both ODS and non-ODS alloys present a similar microstructure, composed of martensite laths and a high density of dislocations in the as-HIPed state.…”
Section: Resultsmentioning
confidence: 99%
“…The oxide dispersion strengthened (ODS) reduced activation ferritic (RAF) steels as a structural constituent in future fusion reactors will have to withstand high temperatures, high heat flux as well as neutron irradiation conditions [1]. Due to its unique microstructure (ultrafine grains containing oxide nanoparticles), the ODS steel has not only excellent high-temperature strength but also thermal stability.…”
Section: Introductionmentioning
confidence: 99%